Pengembangan Portofolio Digital Mahasiswa sebagai Persiapan Karier di Era Society 5.0 - Reyneldis B. Fernandez; Sebastianus Fernandez (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
The development of digital portfolios has become an essential competency for university students as a means of personal branding and preparation for entering the workforce in the Society 5.0 era. However, many students in the English Education Study Program are still unable to develop digital portfolios systematically and professionally. This Community Service Program aimed to enhance students’ competence, knowledge, and self-confidence through a participatory training approach that included lectures, demonstrations, guided practice, mentoring, and evaluation. The results indicated an improvement in participants’ competence in developing digital portfolios, accompanied by increased motivation and self-confidence. The training effectively enabled participants to produce digital portfolios that can be utilized as a personal branding tool and to support their future career development.